Analysis of Transformational Leadership and Organizational Culture on employee performance mediated by Behavior Citizenship of the Organization (Di Yayasan Harapan Tebing Tinggi) - Mila Sukmawardani; Muhammad Toyib Daulay; Yohny Anwar (International Journal of Society and Law, 2024)
The purpose of this study is to analyze and find out the influence of transformational leadership on employee performance Di Yayasan Harapan Tebing Tinggi)as well as analyze the influence of organizational culture on employee performance, the influence of transformational leadership, organizational culture on employee performance mediated by organizational commitment di Yayasan Harapan Tebing Tinggi. This type of research is quantitative descriptive, the research sample is 100 people, and the data analysis uses the SEM (structural equation modeling) method. Overall, from the results and discussions in the study, it is concluded that there is a positive and significant influence between transformational leadership on employee performance, there is a positive and significant influence between organizational culture on employee performance and the variable of Organizational Citizenship Behavior that is able to mediate transformational leadership and organizational culture on employee performance di Yayasan Harapan Tebing Tinggi